Structural and functional neuroimaging findings associated with the use of clozapine in schizophrenia: a systematic review - Garcia,Giovana J. (2015)
Objective: Schizophrenia is one of the most severe psychiatric disorders, and its current treatment relies on antipsychotic medications with only partial effectiveness. Clozapine is an atypical antipsychotic with a specific profile of action indicated for treatment-resistant schizophrenia. Neuroimaging studies assessing the effects of clozapine could help shed light on the neural underpinnings of the effects of this drug in the brain. The objective of this study was to review the available literature on the structural and functional neuroimaging findings associated with use of clozapine. Method: We conducted a systematic review of the indexed literature using the PubMed, BIREME, and ISI Web of Knowledge search engines and the following keywords: clozapine, neuroimaging, computed tomography, MRI, functional magnetic resonance, PET, SPECT, and DTI. Results: A total of 23 articles were included in the review. In structural studies, the use of clozapine was associated with volume reductions in the basal ganglia, especially the caudate nucleus, where functional neuroimaging studies also found decreased perfusion. In the frontal lobe, clozapine treatment was associated with increased gray matter volume and reduced perfusion. Conclusion: The results of the studies reviewed suggest that the use of clozapine is associated with distinctive structural and functional neuroimaging findings that are not shared with other antipsychotics.